2007
DOI: 10.1375/twin.10.2.255
|View full text |Cite
|
Sign up to set email alerts
|

Social Activity and Healthy Aging: A Study of Aging Danish Twins

Abstract: A lthough social and intellectual engagement have been consistently associated with late-life functioning, rather than true causation, these associations may reflect the experiential choices of high functioning individuals (i.e., selection effects). We investigated the association of social activity with late-life physical functioning, cognitive functioning, and depression symptomatology using data from 1112 pairs of like-sex twins who participated in the Longitudinal Study of Aging Danish Twins. Consistent wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
74
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 87 publications
(78 citation statements)
references
References 37 publications
4
74
0
Order By: Relevance
“…The study samples were drawn from two surveys conducted at the Danish Twin Registry (Skytthe et al, 2013) for which data on DNA methylation were already available: the Longitudinal Study of Aging Danish Twins (LSADT) (McGue & Christensen, 2007) and a study of the Extremely Birth Weight Discordant Twins (Frost et al, 2012).…”
Section: Experimental Procedures Study Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…The study samples were drawn from two surveys conducted at the Danish Twin Registry (Skytthe et al, 2013) for which data on DNA methylation were already available: the Longitudinal Study of Aging Danish Twins (LSADT) (McGue & Christensen, 2007) and a study of the Extremely Birth Weight Discordant Twins (Frost et al, 2012).…”
Section: Experimental Procedures Study Samplesmentioning
confidence: 99%
“…The study was initiated in 1995 and surviving twins were followed-up every second year through 2007 (Christensen et al, 1999;McGue & Christensen, 2007). In 1997 and 2007, whole blood samples were collected from same-sex twin pairs, and the samples included in the present study consisted of those 18 monozygotic (MZ) pairs and 25 dizygotic (DZ) pairs, which participated in both the 1997 and the 2007 wave.…”
Section: Experimental Procedures Study Samplesmentioning
confidence: 99%
“…Each survey of the LSADT and the 1905 Cohort Study comprises multidimensional face-to-face interviews focusing on health and lifestyle issues, as well as objective assessments of cognitive and physical abilities. [9][10][11] The Danish Centenarian Study is a nationwide epidemiological survey of all persons living in Denmark who celebrated their 100th birthday during a 14-month period from 1995 to 1996. A year and a half later, 21 participants were still alive and were revisited.…”
Section: Study Populationmentioning
confidence: 99%
“…Analogously, Brown et al (2016), using data from the Victoria Longitudinal Study, found that the engagement in social activities for older adults was related to participation in everyday cognitive activities and in turn to better cognitive performance. Conversely, lack of association between social activity and cognitive functioning along time was found in other studies (McGue and Christensen, 2007;Aartsen et al 2002;Green et al 2008), which used a global measure of cognitive functioning and a variety of specific cognitive tasks.…”
Section: Introductionmentioning
confidence: 63%